REMEDYING THE POLLUTION OF ATHI RIVER IN KENYA - CHIMBINDI, TAKAWIRA (Advances in Social Sciences Research Journal, 2021)
The Athi River, which is 390 km before entering the Indian Ocean, is the second-longest river in Kenya. As it flows through the grasslands and valleys of Kenya, the river forms the majestic Fourteen Falls, meanders through Nairobi, and eventually passes through Tsavo National Park, the largest in Kenya. Here, hippopotamus, crocodiles, and pythons are attracted to the river’s waters and the life it carries. Millions of Kenyans rely on the Athi River for drinking water and irrigation. However, the Athi River also receives large amounts of pollution from Nairobi–an area with a population of over four million people. Along with population growth and rapid urbanization, poor solid waste management is emerging as a key risk for health in Kenya. The river is increasingly choking with uncollected garbage; human waste from informal settlements; industrial waste in the form of gaseous emissions, liquid affluence, and solids waste; agrochemicals, and other wastes especially petrochemicals and metals from microenterprises – the hot sun and overflowing sewers. This situation has occasioned the spread of waterborne diseases, loss of sustainable livelihoods, loss of biodiversity, reduced availability and access to safe potable water, and various toxic substances and heavy metal poisoning, affecting human productivity. The paper is not empirically grounded and its content is a result of desktop research and content analysis of literature, images, and news related to pollution. The paper hopes to provoke further deliberations and empirical research on the river.